The Time of Breakthroughs and Its Testimony – Life and Works of Cassiodorus Senator (Vade Nobiscum, tom XXV/2025: Varia, 2025)
The turn of the fifth and sixth centuries are a period of breakthrough in the history of Europe, both political (creation of tribal states in the territories of former Western Empire) and cultural. Its symptoms are noticeable in the analysis of Cassiodorus Senator’s life. The Historian’s experiences – from his youth in the family of an aristocratic family in Italia, through his service at the court of Theodoric the Great, to his spiritual turn and his foundations of monasteries – can be attributed to the elements of the culture of Antiquity, Middle Ages or to transitional phenomena. A similar tendency can be ascribed to Cassiodorus’ works, including his historical and theological texts.